Narratives of Deception - A Didactic Approach to Serial Literacy - Intveen, Julie

SERI: High-Throughput Streaming Acceleration of Electron Repulsion Integral Computation in Quantum Chemistry using HBM-based FPGAs - Stachura, Philip; Li, Guanyu; Wu, Xin; Plessl, Christian; Fang, Zhenman (2024 34th International Conference on Field-Programmable Logic and Applications (FPL))
The computation of electron repulsion integrals (ERIs) is a key component for quantum chemical methods. The intensive computation and bandwidth demand for ERI evaluation presents a significant challenge for quantum-mechanics-based atomistic simulations with hybrid density functional theory: due to the tens of trillions of ERI computations in each time step, practical applications are usually limited to thousands of atoms. In this work, we propose SERI, a high-throughput streaming accelerator for ERI computation on HBM-based FPGAs. In contrast to prior buffer-based designs, SERI proposes a novel streaming architecture to address the on-chip buffer limitation and the floorplanning challenge, and leverages the high-bandwidth memory to overcome the bandwidth bottleneck in prior designs. Moreover, to meet the varying computation, bandwidth, and floorplanning requirements between the 55 canonical quartet classes in ERI calculation, we design an automation tool, together with an accurate performance model, to automatically customize the architecture and floorplanning strategy for each canonical quartet class to maximize their throughput. Our performance evaluation on the AMD/Xilinx Alveo U280 FPGA board shows that, SERI achieves an average speedup of 9.80 x over the previous best-performing FPGA design, a 3.21x speedup over a 64-core AMD EPYC 7713 CPU, and a 15.64x speedup over an Nvidia A40 GPU. It reaches a peak throughput of 23.8 GERIS ($10^9$ ERIs per second) on one Alveo U280 FPGA. SERI will be released soon at https://github.com/SFU-HiAccel/SERI.

Kulturelle Teilhabe und innovative Preiskonzepte. Einblicke in ein interdisziplinäres Forschungsprojekt - Flath, Beate; Kundisch, Dennis; Wünderlich, Nancy V. (neues museum)

On the global impact of Erich Mendelsohn’s architecture. Sergio Larraín’s Oberpaur building in Santiago and the beginnings of modernist architecture in Chile - Silvestri, Marco (Positioning: Erich Mendelsohn and the Built Heritage of the 20th Century)

Hans Lenk (1985): Die achte Kunst - Meier, Heiko (Sport und Gesellschaft)

“Orden y traza”. Städtebau im Vizekönigreich Peru zwischen Regulierungspolitik und Architekturtheorie - Silvestri, Marco (Cultura architettonica nell’Impero di Carlo V. Storia globale, microstoria, storiografia (1519-1556))

Highly dynamic force control for experimental vibration analysis with an electrodynamic shaker Hochdynamische Kraftregelung für die experimentelle Schwingungsanalyse mit einem elektrodynamischen Shaker - Lüke, Christopher; Trächtler, Ansgar (Forschung im Ingenieurwesen)
Abstract A new control method aims at the precise high dynamic control of the force signal for experimental vibration analysis, which is generated by an electrodynamic shaker. A bending beam is used as a nonlinear test object. A design and a surrogate model of the test rig are shown and parameterized based on test rig measurements. The force control algorithm using input/output linearisation is described and implemented in Matlab/Simulink for simulative validation studies. Conclusions drawn from the mathematical description of the problem as well as simulation results show that the design of the contact between shaker and test object is crucial to achieve a high control bandwidth and at the same time reduce the energy consumption of the shaker. This leads to the practical application using a novel damping contact element. Finally, experimental test rig results are presented which show a closed loop bandwidth of at least 250 Hz for sinusoidal excitation signals.

„Ich mag an mir …“ - Grimminger-Seidensticker, Elke (Die GRUNDSCHULZEITSCHRFT)

Cost Analysis for a Small-Scale Hybrid, Hydrogen-Based PV Energy System - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 41st European Photovoltaic Solar Energy Conference)

Analysis and Demand Side Management of East African Rural Microgrids: Modelling and Experimental study - Philipo, Godiana Hagile

Wissenschaftsdidaktik: Kommunikation, Praktiken, Artefakte – und Sinn - Scharlau, Ingrid (Psychologieunterricht)

Von Prozessen der Formfindung in der Keramik - Frontzek, Helena (Schnittstelle Kunstunterricht: Skulptur – Material – Prozess)
Innerhalb eines skulpturalen Abstraktionsprozesses kann die Frage aufkommen, wie neue plastische Formen geschaffen werden können, wenn diese nicht naturorientiert abbilden. Um jedoch abstrakten Skulpturen eine Gestalt verleihen zu können, eröffnet sich eine intensive Formsuche. Diese wird exemplarisch anhand der künstlerischen Masterarbeit zur »Aktualisierung von Ovids Metamorphosen« beleuchtet, welche im Außenatelier, dem Projekt- und Ausstellungsraum der Bildhauerei in der Universität Paderborn, im Juli 2023 präsentiert wurde. Schließlich wird eine Auswahl dieser keramischen Skulpturen hinsichtlich abstrakter Formfindungsstrategien vorgestellt.
Keywords: Bildhauerei; Skulptur; zeitgenössische Kunst; Ausstellung; Formfindung; künstlerisches Handeln; didaktische Konzeptionen; Keramik; Metamorphose; Verwandlung; Materialverwandlung; Ovid; Pygmalion-Effekt

Duale Ausbildungsqualität: Eine kritische Auseinandersetzung mit dem Forschungsstand vor dem Hintergrund neuer Bedarfe und Möglichkeiten - Deutscher, Viola; Abele, Stephan; Festner, Dagmar; Findeisen, Stefanie; Goller, Michael; Harteis, Christian; Rausch, Andreas; Seifried, Jürgen (bwpaed online)

Expulsion prevention in resistance spot welding of dissimilar joints with ultra-high strength steel: An analysis of the mechanism and effect of preheating current - Yang, Keke; El-Sari, Bassel; Olfert, Viktoria; Wang, Zhuoqun; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing Processes)
The widespread adoption of ultra-high strength steels, due to their high bulk resistivity, intensifies expulsion issues in resistance spot welding (RSW), deteriorating both the spot weld and surface quality. This study presents a novel approach to prevent expulsion by employing a preheating current. Through characteristic analysis of joint formation under critical welding current, the importance of plastic material encapsulation around the weld nugget (plastic shell) at high temperatures in preventing expulsion is highlighted. To evaluate the effect of preheating on the plastic shell and understand its mechanism in expulsion prevention, a two-dimensional welding simulation model for dissimilar ultra-high strength steel joints was established. The results showed that optimal preheating enhances the thickness of the plastic shell, improving its ability to encapsulate the weld nugget during the primary welding phase, thereby diminishing expulsion risks. Experimental validation confirmed that by employing the optimal preheating current, the maximum nugget diameter was enhanced to 9.42 mm, marking an increase of 13.4 % and extending the weldable current range by 27.5 %. Under quasi-static cross-tensile loading, joints with preheating demonstrated a 7.9 % enhancement in maximum load-bearing capacity compared to joints without preheating, showing a reproducible and complete pull-out failure mode within the heat-affected zone. This study offers a prevention method based on underlying mechanisms, providing a new perspective for future research on welding parameter optimization with the aim of expulsion prevention.
Keywords: Expulsion Resistance spot welding Finite element modelling Preheating Weldable current range Ultra-high strength steel

Electron iso-density surfaces provide a thermodynamically consistent representation of atomic and molecular surfaces - Alibakhshi, Amin; Schäfer, Lars V. (Nature Communications)
Abstract The surface area of atoms and molecules plays a crucial role in shaping many physiochemical properties of materials. Despite its fundamental importance, precisely defining atomic and molecular surfaces has long been a puzzle. Among the available definitions, a straightforward and elegant approach by Bader describes a molecular surface as an iso-density surface beyond which the electron density drops below a certain cut-off. However, so far neither this theory nor a decisive value for the density cut-off have been amenable to experimental verification due to the limitations of conventional experimental methods. In the present study, we employ a state-of-the-art experimental method based on the recently developed concept of thermodynamically effective (TE) surfaces to tackle this longstanding problem. By studying a set of 104 molecules, a close to perfect agreement between quantum chemical evaluations of iso-density surfaces contoured at a cut-off density of 0.0016 a.u. and experimental results obtained via thermodynamic phase change data is demonstrated, with a mean unsigned percentage deviation of 1.6% and a correlation coefficient of 0.995. Accordingly, we suggest the iso-density surface contoured at an electron density value of 0.0016 a.u. as a representation of the surface of atoms and molecules.

On the Theoretical Quantification of Radii of Atoms in Molecules - Alibakhshi, Amin; Schäfer, Lars V. (The Journal of Physical Chemistry A)

Steuerwettbewerb als Chance - Birnbaum, Kirsten; Heckemeyer, Jost H.; Linau, Annette; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Time perspectives and collaborative performance in creative tasks - Auer, Thorsten Fabian; Hoppe, Julia Amelie; Thommes, Kirsten (Journal of Organizational Effectiveness: People and Performance)
Purpose The relationship between variation in time perspectives and collaborative performance is scarcely explored, and even less is known about the respective mechanisms that lead to varying task performance. Thus, we aim to further the literature on time perspectives and collaborative performance, shedding light on the underlying behavioral patterns. Design/methodology/approach We report a quasi-experiment analyzing the impact of past, present and future orientation variation in dyads ( N = 76) on their quantitative and qualitative performance when confronted with a simple incentivized creative task with constraints. Subsequently, we offer a qualitative analysis of comments given by the participants after the task on the collaboration. Findings Results indicate that a dyad's elevation of past orientation and diversity in future orientation negatively affect collaborative performance. At the same time, there is a positive effect of elevation of future orientation. The positive effect is driven by clear communication and agreement during the task, while the negative effect arises from work sharing and complementation. Practical implications This study provides insights for organizations on composing individuals regarding their temporal focus for collaborative tasks that should be executed rapidly and require creative solutions. Originality/value Our study distinguishes by considering the composition of past, present and future time perspectives in dyads and focuses on a creative task setting. Moreover, we explore the mechanisms in the dyads with a substantial elevation of/diversity in future orientation, leading to their stronger/weaker performance.
Keywords: Organizational Behavior and Human Resource Management

Approach for the Reliable and Virtual Design of Mechanical Joints in an Uncertain Environment - Einwag, Jonathan-Markus; Goetz, Stefan; Wartzack, Sandro (DS 133: Proceedings of the 35th Symposium Design for X (DFX2024))

Train Once Apply Anywhere: Effective Scheduling for Network Function Chains Running on FUMES - Blöcher, Marcel; Nedderhut, Nils; Chuprikov, Pavel; Khalili, Ramin; Eugster, Patrick; Wang, Lin (Proceedings of the IEEE International Conference on Computer Communications (INFOCOM))